Bauhinia championii flavone inhibits apoptosis and autophagy via the PI3K/Akt pathway in myocardial ischemia/reperfusion injury in rats - Jian J; Xuan FF; Qin FZ; Huang RB (Dove Medical Press, 2015)
Jie Jian,1,* Feifei Xuan,2,* Feizhang Qin,2 Renbin Huang21Department of Pharmacology, Guilin Medical University, Guilin, Guangxi, 2Department of Pharmacology, Guangxi Medical University, Nanning, People’s Republic of China*These authors contributed equally to this workAbstract: This study aimed to determine the effects of Bauhinia championii flavone (BCF) on myocardial ischemia/reperfusion injury (MI/RI) in rats and to explore potential mechanisms. The MI/RI model in rats was established by ligating the left anterior descending coronary artery for 30 minutes, then reperfusing for 3 hours. BCF at 20 mg/kg was given 20 minutes prior to ischemia via sublingual intravenous injection, with 24 µg/kg phosphoinositide 3-kinase inhibitor (PI3K; wortmannin) as a control. The creatine kinase-MB and nitric oxide content were assessed by colorimetry. The levels of mitochondrial permeability transition pores and tumor necrosis factor alpha were determined by an enzyme-linked immunosorbent assay. Cardiomyocyte apoptosis was detected by the terminal deoxynucleotidyl transferase dUTP nick end labeling assay. Additionally, the expression of PI3K, endothelial nitric oxide synthase, caspase-3, and Beclin1 was analyzed by fluorescence quantitative polymerase chain reaction and Western blotting, respectively. Akt and microtubule-associated protein 1 light chain 3-II protein levels were also evaluated. Pretreatment with BCF significantly decreased the levels of creatine kinase-MB, tumor necrosis factor alpha, and mitochondrial permeability transition pores, but increased the nitric oxide content. Furthermore, BCF inhibited apoptosis, downregulated caspase-3, Beclin1, and microtubule-associated protein 1 light chain 3-II, upregulated PI3K, and increased the protein levels of phosphorylated Akt and endothelial nitric oxide synthase. However, all of the previously mentioned effects of BCF were blocked when BCF was coadministered with wortmannin. In conclusion, these observations indicated that BCF has cardioprotective effects against MI/RI by reducing cell apoptosis and excessive autophagy, which might be related to the activation of the PI3K/Akt signaling pathway.Keywords: Bauhinia championii flavone, myocardial ischemia/reperfusion injury, apoptosis, autophagy, PI3K/Akt